Grafting to boost mango production - Kumawat, P C; Singh, Shalandra (Indian Horticulture, 2019)
Grafting is most important technique for multiplying mango. It is generally done in rainy season when humidity is high. It can be done in other months in protected conditions. In rural areas, installing polyhouse is costly and occupies space. So only option is to do grafting in rainy season only. The main threat in rainy season is that rain water can enter in grafted parts of the plant and can create condition for fungal infection. There are some areas in our country, where humidity is low even in the rainy season.